Facile synthesis of polyamide 6 (PA6)-based thermoplastic elastomers with a well-defined microphase separation structure by melt polymerization. Issue 11 (27th February 2018) - Yuan, Ruchao; Fan, Shuo; Wu, Dequn; Wang, Xueli; Yu, Jianyong; Chen, Lijun; Li, Faxue
Abstract : A facile melt polymerization method for polyamide-6 based thermoplastic elastomers with a well-defined microphase separation structure is proposed. Abstract : A facile "2-step" melt polymerization method with high efficiency, easy accessibility, little pollution and low cost was proposed to fabricate thermoplastic elastomers (TPAEs) composed of polyamide 6 (PA6) and poly(tetramethylene glycol) (PTMG). To elucidate the thermal properties of these TPAEs measured by differential scanning calorimetry (DSC), a three-phase system was represented: a "pure" PA6 crystalline phase, a phase-separated mesophase (soft phase domains embedded in a PA6 ordered phase matrix) and a mixed phase (PA6 disordered phase + soft segments). The X-ray technology, dynamic mechanical analysis (DMA) and transmission electron microscopy (TEM) results offered further support to the morphological structural interpretation. The soft segment weight fraction in the mixed phase ( W SS ) was found to be equal to the overall soft segment weight concentration ( C SS ). The multiple melting transitions ( T M and T MMT ) occurring in these TPAEs were assigned to the disruption of the "pure" PA6 crystalline phase and the phase-separated mesophase, respectively. Additionally, the prepared TPAEs demonstrated better thermal and mechanical properties than PEBAX®, one of the commercial elastomers, presenting the potential to be widely used in various industrial fields.